PENGARUH TEAMWORK DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN YAYASAN TITIAN BUDI LUHUR DI KABUPATEN PARIGI MOUTONG - Pandelaki, Margotje Treisje (Katalogis, 2018)
The study aims to determine and analyze simultaneous influence ofteamwork and work culture on employees’performance at Titian Budi Luhur Foundation in Parigi Moutong District. Method of analysis is quantitative approach with multiple linear regressions. Population and sample involve 49 employees of Titian Budi Luhur foundation in Parigi Moutong District that focus on two business units namely PT. BPR Binartha Luhur and Budi Luhur Saving and Loan Cooperative.The study finds that teamwork and work culturesimultaneously and partially influence employees’ performance in PT. BPR Binartha Luhur and Budi Luhur Saving and Loan Cooperative significantly withR2 value of 0,583 or58,3 %. This show that independent variables of teamwork and work culture influence the employees’ performance of 58,3% while 41,7% influenced by other variables that are not studied.